SIKAP PETANI TERHADAP PROGRAM ASURANSI USAHATANI PADI (AUTP) DI KECAMATAN BULU KABUPATEN SUKOHARJO - Farry Primandita; Suwarto Suwarto; Sutarto Sutarto (Universitas Sebelas Maret, 2018)
This research aims to analyze the factors that affect farmer attitudes on the rice farming insurance program (AUTP), analyze how is farmer attitudes in AUTP program, analyze the relationship between factors affecting farmer attitudes and farmer attitudes toward the AUTP program, and analyzed differences in farmer attitudes based on the area of insured land, employment outside the agricultural sector and ownership of livestock assets in the AUTP Program. The basic method of research used is quantitative research method with survey technique. The selection of research sites was done purposively. Sampling is taken by proportional random sampling technique and multistage cluster sampling method. To know the correlation between the factors that influence the formation of farmer attitude with his attitude toward AUTP program used Rank Spearman correlation test, while to know whether there is difference of attitude of farmer use U Mann-Whitney different test. The result of the research shows that farmers expressed their willingness to support the AUTP program. There is a significant relationship between the experience of farming (X1), the influence of others who are considered important (X2) and non formal education (X4) with farmers attitude toward the AUTP (Y) program. While there is no significant relationship between formal education (X3) and media exposure (X5) with farmers attitude toward AUTP (Y) program. There is no difference in the attitude of farmers when viewed from the size of the land that is insured, jobs outside the agricultural sector as well as ownership of livestock assets.